How to Explain Financial Disagreements in Families - Popova, Polina (Journal of Economic Sociology, 2017)
Western literature identifies financial conflict as the main predictor of divorce in families and the most difficult and prolonged issue for spouses. However, the determinants of their occurrence remain a “blind spot” in the vast body of research devoted to marital conflicts and financial management. This article seeks to conceptualize financial conflict and to explain how it arises. The first part examines empirical studies of family conflicts and the role of money problems. Then, drawing on theories of family systems, family stress, social exchange, distribution of benefits, and role theory, the second part looks at the conflict formation process and possible predictors of financial conflict in the family. The third part of the review is devoted to a detailed examination of three factors in conflict formation at a theoretical level. The first of these is financial management and the opposition of independent strategies and pooling mechanisms. Continuing the theme of financial control, the next factor relates to concepts of power and how the grounds for its construction within a household contribute to financial conflict. The final factor is the gendered division of labor, which, according to a number of studies, is a key factor in marital dissatisfaction (especially for women) and the consequent emergence of conflict. The author concludes that these three factors are interrelated and require empirical verification as predictors of financial conflict in families.